Assessment and assessment as a means of motivation for learning a foreign language (Journal of Science-Innovative Research in Uzbekistan, 2024)
The importance of control at different stages of learning a foreign  language is emphasized. The need for objective assessment and marking during  learning is substantiated, 13 since there is a close relationship between assessment  and the formation, maintenance and strengthening of motivation in mastering a  foreign language. It is concluded that an objective, comprehensive assessment is an  important motivating stimulus for a student and an effective tool in a teacher’s arsenal